Body mass index in ambulatory children with cerebral palsy: A cohort study. (April 2016) - Pascoe, Jessica; Thomason, Pam; Graham, H. Kerr; Reddihough, Dinah; Sabin, Matthew A
Abstract : Aim: Children with cerebral palsy (CP) have reduced levels of physical activity compared with children without physical disability and experience risk factors for becoming overweight or obese. In the Australian CP population, there is little information available about the weight status of children with CP. The aims of this study were to compare the distribution of body mass index (BMI) in a cohort of ambulant children with CP with the BMI distribution of Australian children and explore the relationship between BMI and gross motor function. Methods: A retrospective cohort study of 587 children with CP Gross Motor Function Classification System (GMFCS) levels I–III who attended a Gait Laboratory between July 1995 and January 2012 was carried out. The BMI and Z ‐score were calculated at each assessment. Data were grouped into the categories of underweight, healthy, overweight and obese according to age‐specific and sex‐specific percentiles. Results: There were 348 boys and 240 girls with a mean age 11.2 (standard deviation 3.2) years. Mean BMI Z ‐score was 0.11 (standard deviation 1.33). Seven percent of children were underweight, 73.6% healthy, 7.3% overweight and 12.1% obese. This was similar to the distribution of children without disability. The largest percentage of children in the healthy group were classified GMFCS I. The largest percentage of children in the obese group were classified GMFCS III. Conclusions: In this cohort, 19.4% of ambulant children with CP were overweight or obese. This is of concern as BMI may impact on the outcomes of surgical intervention and rehabilitation. Further research is needed to determine the consequences of obesity for children with CP.